Asia Pacific regionalism. Readings in international economic relations - GARNAUT, Ross (Harper Educational, 1994)
Theory of regionalism and multilateralism is discussed and applied to Asia-Pacific economic developments, with chapters on specific regions, and their place in the world context. With index and numerous tables. The contributors are academics, economists and executives from Australia, the US, India, Thailand, Singapore, Indonesia, Hong Kong, Japan and Korea. The editors teach at the ANU.